Artikulasi Ilmu Nahwu Dalam Kehidupan (Studi Analisis Makna I’rob Kitab Al-Jurumiyah Menggunakan Semantika Dalalah Lafzhiyah dalam Ushul Fikih) - Ahmad . (STAI Syaichona Moh. Cholil Bangkalan, 2019)
In the environment of the Islamic Boarding School Nahwu the basis for the scientific foundation of Islam. The Nahwu book that is often used by almost the majority of Islamic boarding schools is al-Ajurumiyah (read; Jurumiyah). In the discussion of this jurumiyah book there is a discussion about I'rob, namely a discussion of changes in a sentence caused by changes in ‘amil (factors) that affect it. This study uses the semantics of language research methods using lafzhiyyah dalalah contained in ushul fiqh. The purpose of this study is to uncover the scope of the articulation of a language that can be interpreted in a broader meaning, not only in the grammatical meaning of language, but also in the meaning of life. The analysis technique of this research uses interpretive techniques, namely researchers interpreting the object of discussion and research using theoretical studies used according to the researcher perspective. The results of this study reveal that I'rob can be articulated in the meaning of daily life, along with its I'rob signs. I’rob jazm means constant and silent which has the sign of I’rob breadfruit (silence); meaning someone who is just silent, stand by (breadfruit/silent) then the position will be stagnant. I’rob khofazh (low, Jar; attractive) means low has the sign of I’rob kasroh (breaking, damaging), meaning that someone whose job is identical to damaging and breaking then his position will be in a low position (bottom). I’rob nashob means the same, standard, flat which has the sign of fathah (opening); it means someone who has the behavior of fathah (opening) then the position will be the same, equal to the average person. I’rob rofa ’means height, fly, lost has the sign I’rob dlommah (proclaim); meaning someone who wishes to be in the position of rofa '(high and fly) then he must have the behavior of dlommah; namely the behavior of gathering, gathering knowledge, gathering friends, relationships, cooperation, followers, including collecting assets and positions. Thus, a person can have a high degree.